Ideology, culture, and national unity under Soekarno’s leadership - Cahyadi, Indrawan; Yunani, Ahmad; Dachlan, Muhammad; Suhendra, Ahmad; Turokhmah, Novia (Faculty of Social and Political Science, Universitas Airlangga, 2025)
This article explores President Sukarno’s cultural politics in shaping the ideological framework, mobilizing tradition, and fostering national unity in the early Republic of Indonesia (1945–1965). Sukarno’s articulation of Pancasila went beyond a mere political manifesto by embedding the five principles in cultural performances, state-sponsored rituals, and heritage initiatives. Through major exhibitions, architectural projects, and mass media campaigns, Sukarno mobilized folklore, traditional arts, and popular culture to construct a shared national narrative. Furthermore, the Nasakom doctrine exemplifies his efforts to integrate nationalism, religion, and communism into a cohesive cultural narrative, reducing ideological divisions and formalizing pluralist discourses. Using qualitative research with discourse analysis of speeches, policy decrees, and contemporary media reports—and grounded in Gramscian cultural hegemony theory—this study unpacks the mechanisms of cultural governance under Sukarno. Findings suggest that these cultural strategies played a significant role in consolidating state authority, fostering a sense of collective identity, and leaving a lasting imprint on Indonesian civic culture beyond Sukarno’s presidency. This article contributes to scholarship on postcolonial nation-building by bridging political history and cultural studies, offering new insights into the performative dimensions of early Indonesian statehood.